PENGARUH PELEPASAN INFORMASI REKAM MEDIS DALAM MENJAMIN ASPEK HUKUM KERAHASIAAN REKAM MEDIS DI RUMAH SAKIT FMC BOGOR - Zaenal Abidin; Yuyun Yunengsih (Bajang Institute, 2021)
Health care facilities are responsible for protecting health information contained in medical records against the possibility of loss, damage, counterfeiting and unauthorized access. Overall, security, privacy, confidentiality and safety are devices that fortify information in medical records. The purpose of this study was to review the effect of the release of medical record information about the implementation of confidentiality, privacy and information security standards about medical record documents at FMC Bogor Hospital. This type of research is qualitative descriptive. The analysis of the data used is the distribution of frequency and also the narrative of the results of the interview conducted. From the results of research conducted at FMC Bogor Hospital has been optimal and has implemented SOP. Advice for hospital agencies in maintaining the confidentiality and security of patient information at FMC Bogor Hospital, preferably for recording loans or to release information for the 3rd party in documenting should BOGOR FMC Hospital use computerized documenting to be safer and easier for data calculation, documenting aims as a form of evidence in case of future demands.